Verlorenvlei vernacular : a structuralist analysis of Sandveld folk architecture - Gribble, John (Department of Archaeology, 2016)
A sample of 41 vernacular houses from the Verloenvlei and Lange Vlei valleys in the Sandveld on the Cape West coast, have been subjected to a structuralist analysis of their form. As elements of human material culture these houses represent the physical objectification of invisible culture. They are the products of a culturally dictated mental process of design, and in their form reflect the successful mediation by their creators of a set of binary oppositions common to all human experience. The mental rules that guide this process of design, and therefore account for the physical form of the object, are called the artifactual competence. Because, as a product of this competence, an artifact has implicit within its form the set of rules that account for its being, it is theoretically possible, through an inductive analysis of artifactual form, to isolate this set of relational rules. The houses in the sample were all carefully recorded and then compared and contrasted. This resulted in the creation of a statement of architectural competence for Verlorenvlei vernacular architecture, based upon which an explanation of its function as an element of human material culture, and a participant in human social relations was attempted.